Basement topography and fresh-water resources of the coastalBasement topography and fresh-water resources of the coastal aquifer at Acapetahua, Chiapas, Mexico - Eva Sánchez; Gerardo Bocanegra; Birgit Steinich, (Geofísica Internacional, 1999)
The coastal aquifer of Acapetahua, Chiapas, southeastern Mexico, consists of one hydrostratigraphic unit composed of continental sediments overlying a crystalline basement. Twenty-four resistivity soundings were conducted and fifty-one water samples were taken in order to determine basic aquifer characteristics such as aquifer geometry and fresh water reserves. The basement topography in the study area is characterized by hills and deep valleys with highly variable basement depths ranging from less than ten meters to several hundreds of meters below surface. Basements hills reduce the aquifer’s thickness considerably along a zone at distances between 4 and 15 km from the coastline. The location of the transition zone between sea and fresh water coincides in space with the basement crests. These crests represent the limit of the fresh-water part of the aquifer in the near coastal region. Based on the aquifer’s geometry determined from resistivity models, and total dissolved solids of the water samples, a maximum value for the pore volume saturated with fresh water in the aquifer of Acapetahua was estimated at 75 km3.